Emergence of 16S rRNA Methylase Gene rmtB in Salmonella Enterica Serovar London and Evolution of RmtB-Producing Plasmid Mediated by IS26 - Wang, Jing; Wang, Zhen-Yu; Wang, Yan; Sun, Fan; Li, Wei; Wu, Han; Shen, Peng-Cheng; Pan, Zhi-Ming; Jiao, Xinan (Frontiers in Microbiology, 2021)
This study aimed to characterize 16S rRNA methylase genes among Salmonella and to elucidate the structure and evolution of rmtB-carrying plasmids. 158 Salmonella isolates from one pig slaughterhouse were detected the presence of 16S rRNA methylase genes, two (1.27%) Salmonella London isolates from slaughtered pigs were identified to carry rmtB. They were resistant to gentamicin, amikacin, streptomycin, ampicillin, tetracycline, florfenicol, ciprofloxacin, and sulfamethoxazole/trimethoprim. The complete sequences of RmtB-producing isolates were obtained by PacBio single-molecule real-time sequencing. The isolate HA1-SP5 harbored plasmids pYUHAP5-1 and pYUHAP5-2. pYUHAP5-1 belonged to IncFIBK plasmid and showed high similarity to multiple IncFIBK plasmids from Salmonella London in China. The rmtB-carrying plasmid pYUHAP5-2 contained a typical IncN-type backbone, and the variable region comprising several resistance genes and an IncX1 plasmid segment was inserted in the resolvase gene resP and bounded by IS26. The sole plasmid in HA3-IN1 designated as pYUHAP1 was a cointegrate of plasmids from pYUHAP5-1-like and pYUHAP5-2-like, possibly mediated by IS26 via homologous recombination or conservative transposition. The structure differences between pYUHAP1 and its corresponding part of pYUHAP5-1 and pYUHAP5-2 may result from insertion, deletion or recombination events mediated by mobile elements (IS26, ISCR1 and ISKpn43). This is the first report of rmtB in Salmonella London. IncN plasmids are efficient vectors for rmtB distribution and are capable to evolve by reorganization and cointegration. Our results further highlight the important role of mobile elements particularly IS26 in the dissemination of resistance genes and plasmid evolution.